FREQUENCY OF COMMON CAUSES OF SEVERE HYPERBILIRUBINEMIA IN NEONATES LEADING TO EXCHANGE TRANSFUSION - MUHAMMAD, B; NARGIS, T; SHAHEEN, R; JEHANZEB, S (Biological and Clinical Sciences Research Journal, 2023)
Neonatal often have hyperbilirubinemia, which may become severe if left untreated. Severe hyperbilirubinemia in neonates that necessitates exchange transfusions may lead to "kernicterus," which has a high risk of morbidity. This descriptive cross-sectional research examined the medical records of sixty newborns who had exchange transfusions at HMC Peshawar between March 2021 and March 2022 and weighed more than two kilos. There were 22 (36%) females and 38 (64%) males in the group. With 37.2% of cases, ABO incompatibility was the most common reason for exchange transfusions. Other causes, such as cephalohematoma and Crigler-Najjar syndrome, were followed by unidentified causes (26.5%), Rh incompatibility without immune hydrops (15.2%), sepsis (08.3%), and urinary tract infections (05.2%). Exclusive breastfeeding and vaginal deliveries were associated variables. It was discovered that the average serum bilirubin level was 28.5 mg/dl (SD = 09.02). The objective of our study was to identify and quantify the most frequent reasons babies needing exchange transfusions have severe hyperbilirubinemia. This study was conducted in the Department of Peaderitcs HMC Peshawar between March 2021 and March 2022. The causes of severe hyperbilirubinemia in neonates needing an exchange transfusion were investigated in this research using a descriptive cross-sectional methodology. Medical records from HMC Peshawar served as the primary source of information. In all, 60 infants weighing over two kilograms received exchange transfusions within the allotted period. The primary emphasis of the data extraction method was on variables such as serum bilirubin levels, linked diseases, gender, and the cause of hyperbilirubinemia. The causes included ABO incompatibility, Rh incompatibility without immune hydrops, sepsis, urinary tract infection, and cephalohematoma. Further information was also gathered on the kind of feeding and the mode of delivery. Frequencies, percentages, averages, and standard deviations were computed using statistical techniques, mostly descriptive statistics. The results were then examined about the study’s objectives. Twenty-two (36%) and 38 (64%) of the sixty neonates studied for this research were female. ABO incompatibility was shown to be the most common cause of severe hyperbilirubinemia necessitating exchange transfusion, explaining 22 (37.2%) instances. In decreasing order of frequency, the other reasons were: sepsis, 5 (8.3%); urinary tract infection, 3 (5.2%); unidentified causes, 16 (26.5%); Rh incompatibility without immune hydrops, 9 (15.2%); and other causes such as cephalohematoma and Crigler-Najjar syndrome, 2 (3.3%). One interesting finding was that newborns born vaginally and those nursed exclusively were more likely to need an exchange transfusion. The average blood bilirubin level throughout the group was 28.5 mg/dl, with a standard deviation 9.02. This research emphasizes the need to watch for ABO incompatibility in neonates, particularly those delivered vaginally, as it is significantly linked to the requirement for exchange transfusions. The most common reason for exchange transfusions for hyperbilirubinemia was found to be ABO incompatibility. Adolescents who were nursed exclusively, male, and born vaginally were more likely to need an exchange transfusion. Neonatal with ABO incompatibility would need close observation after discharge, particularly if they were vaginally born.